2021
DOI: 10.3390/su132313422
|View full text |Cite
|
Sign up to set email alerts
|

Public Acceptability of Policy Interventions to Reduce Sugary Drink Consumption in Urban Vietnam

Abstract: This study aims to assess the public acceptability of interventions to reduce sugary drinks in Vietnam, identify the key determinants, and develop a classification of consumers. A cross-sectional survey with 263 urban consumers evaluated perceptions of four potential interventions: restricting choice, taxation, nudging, and labeling. Thereby, specific attention was devoted to perceived intrusiveness and (personal and societal) effectiveness, as well personal characteristics, including Confucius values. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 90 publications
0
1
0
Order By: Relevance
“…The rst mechanism, which captures the extent to which the public believes the default nudge to be effective at achieving the desired shift in behavior, has been found to be one of the strongest predictors of nutrition policy acceptance in previous studies [25,26], including speci cally for nudges to shift food choices [27,28]. Perceived intrusiveness, or the extent to which people believe the default nudge to limit freedom of choice, is another salient mechanism that has been found to mediate acceptance of a range of nutrition policies [24,26,29]. Finally, this study examines the impact of self-reported engagement in the behavior that is targeted by each nudge, as this has also been found to mediate nutrition policy acceptance [6].…”
Section: Introductionmentioning
confidence: 99%
“…The rst mechanism, which captures the extent to which the public believes the default nudge to be effective at achieving the desired shift in behavior, has been found to be one of the strongest predictors of nutrition policy acceptance in previous studies [25,26], including speci cally for nudges to shift food choices [27,28]. Perceived intrusiveness, or the extent to which people believe the default nudge to limit freedom of choice, is another salient mechanism that has been found to mediate acceptance of a range of nutrition policies [24,26,29]. Finally, this study examines the impact of self-reported engagement in the behavior that is targeted by each nudge, as this has also been found to mediate nutrition policy acceptance [6].…”
Section: Introductionmentioning
confidence: 99%